Erythropoietin treatment in anaemic patients at the Nephrology Unit of the Steve Biko Academic Hospital - a retrospective, cross-sectional study - Kok, Elandre (University of Pretoria, 2020)
Anaemia in chronic kidney disease (CKD) mostly results from a decrease in the production of erythropoietin (EPO) by the failing kidney. CKD progression requires treatment with erythropoiesis-stimulating agents and iron supplementation to ensure sufficient erythrocyte production. Best clinical practice guidelines should be adhered to in managing CKD to reduce morbidity and mortality related to anaemia associated cardiovascular disease. Likewise, guideline deviations create an increased strain on the resources of the treatment facility. It is uncertain to which extent these guidelines are followed by Nephrology Units in the public healthcare sector, or whether the documented international trends are prevalent locally due to the paucity of local data, and therefore further investigation is warranted. This study aimed to assess treatment trends in managing anaemia in CKD patients at the Steve Biko Academic Hospital (SBAH).